Antioxidant Responses Induced by Short-Term Activity–Estivation–Arousal Cycle in Pomacea canaliculata - Giraud-Billoud, Maximiliano; Campoy-Diaz, Alejandra D.; Dellagnola, Federico A.; Rodriguez, Cristian; Vega, Israel A. (Frontiers in Physiology, 2022)
Long-term estivation (45 days) in the apple snail Pomacea canaliculata induces an increase of non-enzymatic antioxidants, as uric acid and reduced glutathione, which constitutes an alternative to the adaptive physiological strategy of preparation for oxidative stress. Here we studied markers of oxidative stress damage, uric acid levels and non-enzymatic antioxidant capacity, enzymatic antioxidant defenses, superoxide dismutase (SOD), catalase (CAT), and glutathione S-transferase (GST) and transcription factors expression (FOXO, HIF1α, and Nrf2) in control active animals, 7-day estivating and aroused snails, in the digestive gland, gill, and lung tissue samples. In the digestive gland, SOD and CAT activities significantly increased after estivation and decreased during arousal. Meanwhile, GST activity decreased significantly during the activity-estivation-arousal cycle. Gill CAT activity increased significantly at 7 days of estivation, decreasing during arousal. In the lung, the CAT activity level increased significantly during the cycle. FOXO upregulation was observed in the studied tissues, decreasing its expression only in the gill of aroused animals during the cycle. HIF1α and Nrf2 transcription factors decreased their expression during estivation in the gill, while in the lung and the digestive gland, both transcription factors did not show significant changes. Our results show that the short-term estivation induced oxidative stress in different tissues of P. canaliculata thereby increasing overall antioxidant enzymes activity and highlighting the role of FOXO regulation as a possible underlying mechanism of the preparation for oxidative stress strategy.